Pollen Morphology of the Four Species Asteraceae - Karbela, Dawa Nure; Anggraini, Dina Novita; Khoerunnisa, Keisya; Lestari, Wulan Putri Dina; Priyanti, Priyanti (Universitas Pattimura, 2025)
Asteraceae has many species and pollen shape varies. Pollen becomes one of the characteristics of the species and data on the morphological characteristics of pollen can help taxonomic data. This study aimed to determine the morphological character of pollen from four species of the Asteraceae. Pollen from Tridax procumbens, Tagetes erecta, Zinnia angustifolia, and Z. elegans was taken from the flower and smeared on a glass object and then dripped with distilled water. Fresh preparations were observed with a fluorescens microscope. The pollen shapes of the four species had monad prolate spheroidal (T. erecta, Z. elegans), monad subsphreoidal (Tr. procumbens), and monad oblate-spheroidal (Z. Angustifolia). Zinnia angustifolia had microechinate pollen ornamentation while another species had echinate pollen ornamentation. The four species had aperture varies, i.e tricolpate (T. erecta, Z. elegans), tetracolporate (Tr. procumberns), and monocolpate (Z. Angustifolia). Tagetes erecta had the biggest diameter pollen (51,405 µm) than the pollen diameter of another species (30,618-36,043 µm). Pollen morphology could differentiate of the four species Asteraceae members.